Effect of Drainage on Certain Chemical Properties of a Heavy Clay Soil and on Tree Nutrition - Yadav, J. S. P. (Indian Forester, 1961)
An investigation into certain chemical properties of a heavy clay soil and tree nutrition under both intensively and poorly drained conditions has been described. The results indicate that draining has caused slight decrease in pH, total nitrogen and organic matter content, especially in the top soil. On the other hand, the studies on nitrogen mobilization, in which the use was made of a specially designed simple technique, revealed a far greater production of available nitrogen in the drained soil evidently due to better aeration and microbial activity. The foliar analyses of the trees growing on the drained and undrained plots suggest that draining has been accompanied by an increased uptake of nitrogen and phosphorus, particularly of the former.